KONTROVERSI ULAMA KONTEMPORER TENTANG KEBERADAAN BANK ASI - Adnan, zulhamdi (At-Tafkir, 2020)
Abstract: The position of the mother who is breastfeeding a baby is the same status as her mother because she is not allowed to marry the woman and her offspring. In Islam, it is called brotherhood. The problem now is milk stored in the ASI Bank which can be used by a baby at any time, how is the law in an Islamic perspective, giving rise to khilafiah among scholars related to the existence of the ASI bank. This study uses a descriptive qualitative research approach, namely document review. Controversial scholars related to the existence of ASI banks. Some scholars allow ASI banks because babies who drink milk from breast milk banks cannot become mahram for women who have breast milk. After all, the prohibited breastfeeding is if they breastfeed directly to suck the nipples of women who have breast milk. Breast milk, like a baby child who suckles his mother directly. Whereas scholars who refuse the existence of ASI bank their reason is that it will cause mixing of nasab, because forbidden milking can occur with the entry of milk into the baby's stomach, even without direct breastfeeding, like a baby who is breastfeeding at his mother directly.